The Role of HCMV and HIV-1 MicroRNAs: Processing, and Mechanisms of Action during Viral Infection - Fruci, Doriana; Rota, Rossella; Gallo, Angela (Frontiers in Microbiology, 2017)
Viruses infect host cells releasing their genome (DNA or RNA) containing all information needed to replicate themselves. The viral genome takes control of the cells and helps the virus to evade the host immune system. Some viruses alter the functions of infected cells without killing them. In some cases infected cells lose control over normal cell proliferation and becomes cancerous. Viruses, such as HCMV and HIV-1, may leave their viral genome in the host cells for a certain period (latency) and begin to replicate when the cells are stressed causing diseases. HCMV and HIV-1 have developed multiple strategies to avoid recognition and elimination by the host’s immune system. These strategies rely on viral products that mimic specific components of the host cells to prevent immune recognition of virally infected cells. In addition to viral proteins, viruses encode short non-coding RNAs (vmiRNAs) that regulate both viral and host cellular transcripts to favor viral infection and actively curtail the host’s antiviral immune response. In this review, we will give an overview of the general functions of microRNAs generated by HCMV and HIV-1, their processing and interaction with the host’s immune system.